Estrategias de promoción de actividades ecológicas en el Bosque Protector Pedro Franco Dávila para el desarrollo del ecoturismo - Plúas Rendón, Ginger Fidelina (2021)
The Palenque canton has a great variety of cultural and natural attractions among which stands out the Pedro Franco Dávila Protected Forest. It is located in the Jauneche area of the Palenque canton in Los Rios province is a forest full of biodiversity and surrounded by friendly people and fighter, with legends that enclose their land. It was declared a protected forest in 1987 by the University of Guayaquil. Its name is due to the researcher, naturist biologist Pedro Franco Davila who conducted a series of investigations on the diversity of flora and fauna that presents the forest, currently serves as a research center of some universities because it is a scientific station. The forest has a biologist who is the person in charge of caring for and providing information about the scientific station. The promotion strategy will offer relevant and innovative information about the Pedro Franco Dávila protective forest of the ecological activities through interactive content, videos about the protective forest on social networks because it is a technique widely used by young people and adults. Among the situations detected, the scarce information that the population has about the benefits that tourism offers was identified, being a fundamental axis to improve the quality of life of its inhabitants. Little promotion of the Pedro Franco Dávila Protected Forest, which causes the low influx of visitors and the outdated information of the Pedro Franco Dávila Protected Forest on web platforms. Among the techniques applied in the collection of information, documentary, descriptive, qualitative and quantitative research was used, deductive, inductive, analytical methods, and the techniques applied was an online survey using the 10-question questionnaire as an instrument.